Maximizing the Electric Vehicles’ Owners Profit Considering Optimal Charging and Discharging Management in the Distribution Networks Using Dynamic Programming - Ali Masoudi; Mohsen Simab; Hamidreza Akbarj; Seyed Amin Saeed; Tahereh Daemi (International Journal of Industrial Electronics, Control and Optimization, 2022)
With an increasing penetration rate of electric vehicles in distribution networks, it is becoming vital to schedule their battery charging/discharging to maintain the network balance and increase the vehicle owners’ profit. Electric vehicles are now considered one of the most important and accessible sources of revenue for their owners since they can be connected to the grid (V2G) as a power source during peak hours. As such, while flattening the power profile, they can improve the voltage drop across the grid buses. If charging/discharging of the vehicles is scheduled irregularly, the power drawn from the phases will become unbalanced, which can cause global outages and impair system stability in addition to increasing the harmonic volume and decreasing power quality. The present paper uses dynamic programming to reduce operating costs and enhance the profits of vehicle owners who participate in the V2G program. This optimization algorithm eliminates the undesirable paths leading to unconventional responses in the search space, which will greatly increase the speed and accuracy by which the optimal response is achieved. This model, along with multi-part tariffs on electricity prices, can lead to the more active participation of vehicle owners and help improve the power quality indices of the electrical parameters of the grid. The proposed method is simulated on a sample distribution network, and the case studies conducted prove the validity of the proposed algorithm.